2019
DOI: 10.2319/080218-559.1
|View full text |Cite
|
Sign up to set email alerts
|

Class II treatment by palatal miniscrew-system appliance: A case report

Abstract: This case shows that using a rapid palatal expander (RPE) and then a pendulum appliance anchored to palatal miniscrews is an option for improving treatment management in a noncompliant patient requiring maxillary expansion and molar distalization in the late mixed dentition. First, an RPE was used to expand the maxillary arch. Then, a modified pendulum appliance was used to distalize the maxillary first permanent molars. Optimal positioning of two palatal miniscrews enabled both appliances to be supported by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The use of the Hyrax RME expander supported by one or two pairs of miniscrews placed on the bone, successfully opened the midpalatal suture. bone-supported devices are a good choice for Rapid Palatal Expansion [12]. Although not all have used the Hyrax type expander.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the Hyrax RME expander supported by one or two pairs of miniscrews placed on the bone, successfully opened the midpalatal suture. bone-supported devices are a good choice for Rapid Palatal Expansion [12]. Although not all have used the Hyrax type expander.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the standardization of the patient's head position and evaluation of the tomography sections could not be faithfully reproduced in the oral cavity. This necessitated the creation of digital positioning guides [10][11][12][13]. In cases of severe transverse deficiency of the maxilla or asymmetry [22], devices such as the MARPE maxillary skeletal expansion (MARPE MSE) or MARPE SL cannot be indicated because the expander screw does not fit in the palate (Figure 25).…”
Section: Discussionmentioning
confidence: 99%
“…After suture analysis, the three-dimensional files (STL and DICOM, Figure 4) were superimposed [10][11][12][13][14]. As described in the literature [5], both files should be of good quality because they provide essential information, such as hard and soft tissue thickness, anatomical variations, and location and trajectory of the This procedure can be performed in any software that accepts the superimposition of the STL and CBCT files and also permits the importation of mini-implants and the MARPE expander screw-in STL format.…”
Section: Anatomical Evaluation and Virtual Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…Placing a miniscrew in limited buccal bone width with inaccurate insertion may result in injury to the roots or cause buccal plate breakage. Furthermore, Lombardo et al [27] reported that when there are space limitations in the insertion site, surgical guides can help to increase the success rate of miniscrews regardless of operator skill level.…”
Section: Discussionmentioning
confidence: 99%